[18F]FDG-PET/CT in patients with bacteremia: Clinical impact on patient management and outcome - Hess, Søren (Frontiers in Medicine, 2023)
Bacteremia is the presence of viable bacteria in the bloodstream, a complicated and potentially dangerous systemic medical condition that may range from asymptomatic and clinically relatively indolent cases to more severe bloodstream infection (BSI) and ultimately life-threatening septic shock with fatal outcome. BSI is classified as simple (bacteremia only) or complex (BSI with metastatic spread), and the morbidity is higher in the latter, probably due to insufficient eradication. Treatment of simple BSI is usually short-term antibiotic courses, whereas complex BSI with metastatic foci requires more advanced treatment including long-term antibiotics or invasive drainage to gain infection control. Thus, identifying metastatic infection has an important clinical impact but remains a challenge; only half of the patients progress to complex BSI, and many patients present without relevant signs or symptoms, so imaging is pivotal. This review summarizes the potential role and recommendations of [18F]FDG-PET/CT in BSI, based on the relatively sparse and heterogeneous literature. [18F]FDG-PET/CT should be considered in suspected complex BSI, in patients at high risk of metastatic spread, and in BSI in ICU patients. [18F]FDG-PET/CT has an impact on patient management, treatment strategy, and patient outcome, mainly by directing the diagnostic process toward more specific diagnostics or by modifying treatment regimens resulting in reduced relapse rates and reduced mortality. Finally, a negative scan may obviate the need for further workup.